2015
DOI: 10.1002/jcsm.12096
|View full text |Cite
|
Sign up to set email alerts
|

Growth differentiation factor‐15 is associated with muscle mass in chronic obstructive pulmonary disease and promotes muscle wasting in vivo

Abstract: BackgroundLoss of muscle mass is a co‐morbidity common to a range of chronic diseases including chronic obstructive pulmonary disease (COPD). Several systemic features of COPD including increased inflammatory signalling, oxidative stress, and hypoxia are known to increase the expression of growth differentiation factor‐15 (GDF‐15), a protein associated with muscle wasting in other diseases. We therefore hypothesized that GDF‐15 may contribute to muscle wasting in COPD.MethodsWe determined the expression of GDF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 38 publications
3
88
0
Order By: Relevance
“…[57][58][59][60][61][62][63] As befits a series of fields that are relatively new and not the main speciality of many practitioners, there was a large number of informative review articles, 64-71 as well as the emergence of reports on patient groups, commentaries, and political campaigns. [57][58][59][60][61][62][63] As befits a series of fields that are relatively new and not the main speciality of many practitioners, there was a large number of informative review articles, 64-71 as well as the emergence of reports on patient groups, commentaries, and political campaigns.…”
Section: E D I T O R I a Lmentioning
confidence: 99%
See 1 more Smart Citation
“…[57][58][59][60][61][62][63] As befits a series of fields that are relatively new and not the main speciality of many practitioners, there was a large number of informative review articles, 64-71 as well as the emergence of reports on patient groups, commentaries, and political campaigns. [57][58][59][60][61][62][63] As befits a series of fields that are relatively new and not the main speciality of many practitioners, there was a large number of informative review articles, 64-71 as well as the emergence of reports on patient groups, commentaries, and political campaigns.…”
Section: E D I T O R I a Lmentioning
confidence: 99%
“…We conducted an analysis of the types of publications in the respective medical sub-specialities that this major cachexia focussed journal, JCSM, has published in the last three calendar years and analysed trends within each sub-discipline. [57][58][59][60][61][62][63] As befits a series of fields that are relatively new and not the main speciality of many practitioners, there was a large number of informative review articles, 64-71 as well as the emergence of reports on patient groups, commentaries, and political campaigns. Furthermore, they are classified into the major medical sub-specialities (including ageing) or are considered multidisciplinary if applicable across a range of specialities.…”
mentioning
confidence: 99%
“…The methodology for this is described elsewhere and is detailed further in the online supplement (22).…”
Section: Mouse Studiesmentioning
confidence: 99%
“…66,67 Likewise, muscle loss disorders frequently occur in 20% of older CHF patients 68 and 30-70% of metastatic cancer patients. 81 In CHF, recent findings 82 postulate a correlation between adiponectin resistance and skeletal muscle impairments. [70][71][72][73] Fulster et al 74 has shown in data from the SICA-HF trial that 20% of CHF patients are affected by muscle wasting.…”
Section: Introductionmentioning
confidence: 99%